Coexisting and mixing phenomena of thermoacoustic and magnetoacoustic waves in water - Kishor, Rahul (2015)
Concurrent generation and mixing phenomenon of thermoacoustic (TA) and magnetoacoustic (MA) waves in water are predicted and observed. A theory unifying TA and MA is further put forward to analyze it. By scaling down the radio frequency in thermoacoustics to the low mega Hertz range and by incorporating appropriately a static magnetic field, TA and MA waves are simultaneously generated in the conductive matter. The two waves propagate concurrently in water and produce dynamic acoustic radiation force due to water absorption. Such dynamic radiation force vibrates the absorbing water and consequently yields acoustic emissions at the inter-modulation frequencies of TA and MA waves, creating mixing effect similar to that of vibro-acoustography. The mixing effect can be potentially utilized to mimic vibro-acoustography imaging without firing external ultrasound towards intrinsic dual-contrast (elasticity and conductivity) imaging.